Status of birth preparedness and complication readiness among pregnant women in rural areas - Chajhlana, Sunil Pal Singh; Prathyusha, T. V. D.; Bhumi, Manoj Aravind; Mahabhashyam, Rama Krishna Narashima; Varaprasada, Maruti Sarma Mannava (International Journal Of Community Medicine And Public Health, 2017)
Background: World Health Organization (WHO) estimated that 529,000 women die annually from maternal causes. Ninety-nine percent of these deaths occur in the less developed countries. Every seven minutes - an Indian woman dies from complication related to pregnancy and child birth. For every woman who dies, 30 more women suffer injuries, infection and disability.Birth-Preparedness and Complication-Readiness (BP/CR) is a package to empower women, her family and the community to promote maternal and neonatal survival. It has been recognized as a standard component of the programs designed to make pregnancy safer. Methods: A cross sectional study was conducted among pregnant women who attended antenatal clinics between May 2014-August 2014 at Rural Health Training Centre (RHTC). A total 274 pregnant women who had given consent for the study have been included in the study. Data was collected by interview in local language and a predesigned and pretested questionnaire. Socio-economic status was assessed according to Modified Kuppuswamy’s classification (as per June 2015 CPI index. BP/CR was calculated by a set of seven indicators which has been developed by the John Hopkin Bloomberg School of Public Health. Results: A total of 274 pregnant women have participated in the study. Only half of pregnant women (54.0) were well prepared by fulfilling atleast four indicators of BPCR. Pregnant women in the age group of >30 years, educational status of pregnant women Occupational status of both pregnant women and their husbands and regular antenatal checks ups and their husbands and joint family have significant associations for well birth preparedness and complication readiness (p<0.0005). Conclusions:Pregnant women in the age group of >30 years, educational status of pregnant women and their husbands and joint family have significant associations for well birth preparedness and complication readiness.